A Pilot Study of the Efficacy of Active Leptospermum Honey for the Treatment of Partial-Thickness Facial Burns. (August 2016) - Duncan, Christina L.; Enlow, Paul T.; Szabo, Margo M.; Tolchin, Eric; Kelly, Robert W.; Castanon, Lourdes; Aballay, Ariel M.
ABSTRACT: OBJECTIVE: Research suggests that active Leptospermum honey (ALH) improves outcomes in patients with partial-thickness burns by enhancing healing and reepithelialization rates, as well as by protecting against antibiotic-resistant microorganisms. This study assessed the effectiveness of ALH gel on healing time, bacterial growth, patient satisfaction, and cost of treatment. DESIGN: Single-arm, prospective case series. SETTING AND PATIENTS: Seven patients (aged 7–64 years) with partial-thickness facial burns were recruited from a northeastern US burn center. INTERVENTION: All patients cleansed their wounds daily with soap and water, after which they applied ALH gel. MAIN OUTCOME MEASURES: Three physicians independently rated healing using wound photography and daily tests for the presence of exudate. Wound cultures on days 1 and 7 (±2 days) assessed bacterial growth. Patients completed a satisfaction survey at the end of treatment, and cost of treatment was calculated. MAIN RESULTS: Healing time ranged from 3 to 14 days (mean, 8.1 days). Wound cultures revealed normal bacterial growth on days 1 and 7 for all patients. Patients rated ALH gel favorably, with the most common complaint of stickiness in 5 patients. One patient experienced transient burning on application that did not interrupt treatment. Average hospital-based cost of treatment was 26.15 per patient. CONCLUSIONS: Healing time was congruent with or better than what would have been expected with standard treatment. Furthermore, despite no antibiotic treatment, wound culture results yielded no abnormal bacterial growth. Finally, patients overall reported satisfaction with treatment. The findings of this study suggest that ALH is a clinically and economically valuable treatment for partial-thickness facial burns.